A Breathable, Passive‐Cooling, Non‐Inflammatory, and Biodegradable Aerogel Electronic Skin for Wearable Physical‐Electrophysiological‐Chemical Analysis. Issue 10 (20th January 2023) - Zhu, Yangzhi; Haghniaz, Reihaneh; Hartel, Martin C.; Guan, Shenghan; Bahari, Jamal; Li, Zijie; Baidya, Avijit; Cao, Ke; Gao, Xiaoxiang; Li, Jinghang; Wu, Zhuohong; Cheng, Xuanbing; et al.
Abstract: Real‐time monitoring of human health can be significantly improved by designing novel electronic skin (E‐skin) platforms that mimic the characteristics and sensitivity of human skin. A high‐quality E‐skin platform that can simultaneously monitor multiple physiological and metabolic biomarkers without introducing skin discomfort or irritation is an unmet medical need. Conventional E‐skins are either monofunctional or made from elastomeric films that do not include key synergistic features of natural skin, such as multi‐sensing, breathability, and thermal management capabilities in a single patch. Herein, a biocompatible and biodegradable E‐skin patch based on flexible gelatin methacryloyl aerogel (FGA) for non‐invasive and continuous monitoring of multiple biomarkers of interest is engineered and demonstrated. Taking advantage of cryogenic temperature treatment and slow polymerization, FGA is fabricated with a highly interconnected porous structure that displays good flexibility, passive‐cooling capabilities, and ultra‐lightweight properties that make it comfortable to wear for long periods of time. It also provides numerous permeable capillary channels for thermal‐moisture transfer, ensuring its excellent breathability. Therefore, the engineered FGA‐based E‐skin can simultaneously monitor body temperature, hydration, and biopotentials via electrophysiological sensors and detect glucose, lactate, and alcohol levels via electrochemical sensors. This work offers a previously unexplored materials strategy for next‐generation E‐skin platforms with superior practicality. Abstract : A breathable, passive‐cooling, non‐inflammatory, biodegradable, and flexible aerogel electronic skin is developed to monitor physical, electrophysiological, and metabolic biomarkers from the human body continuously and simultaneously.